The effect of resistance training on the recovery of serum testosterone levels and some reproductive parameters after aspirin consumption in adult male rats - Milad Khosravi sadr; Esmail Nasiri (Shahid Beheshti University, 2023)
Background and Purpose: Studying the causes of infertility and appropriate interventions to protect male fertility is a valuable help to patients who suffer from infertility. There are various causes that can lead to male fertility disorder, including age, drugs, exposure to environmental toxins, genetic problems, and systemic diseases. Aspirin (acetylsalicylic acid: ASA) is one of the most widely used nonsteroidal anti-inflammatory drugs (NASID) in the world, which reduces male fertility. In addition, physical activity can affect male infertility. The purpose of this study was to investigate the effect of resistance training on serum testosterone levels and some of the most important reproductive parameters in adult male Wistar rats consuming ASA.Materials and Methods: A total of twenty-five adult male Wistar rats were randomly divided into control (n=10, C) and the drug administration groups (n=15, AS). After five weeks, five rats from each group were sacrificed and the effect of ASA consumption on serum testosterone level and male reproductive parameters was investigated. After the period of taking the drug and confirming the impact of the ASA drug, its use was stopped and the remaining rats entered the training period. During the training period, the remaining 10 rats were randomly divided from the AS group into the non-intervention group (n=5, NI) and the resistance training group (n=5, RT). Resistance training was performed three times a week for four weeks. Twenty-four hours after the last training session, rats were sacrificed and serum and tissue samples were collected. t-test was used to analyze the difference between groups in the period of drug use. In the training period, the data were analyzed using a one-way analysis of variance and Tukey's post hoc test at a significance level of less than 0.05 in SPSS 24 software.Results: The findings showed that five weeks of ASA consumption led to a significant decrease in serum testosterone levels and cell counts. (P < 0.05) Also, the number, motility, viability of sperm, TDI, SI, RI, as well as a significant increase in the immature nucleus and fragmentation of sperm DNA were abiserved.(P < 0.001). In addition, it was observed that four weeks of resistance training in RT group rats significantly improved the negative changes of ASA drug use compared to the NI group and accelerated the recovery of these changes to the level of the CI group (P < 0/05). However, no significant changes in sperm motility were observed between the research groups during the training period (P > 0.05).Conclusion: The results of the present study confirm the harmful changes of ASA drug on testosterone hormone and male reproductive parameters. In addition, the findings showed that resistance training may improve and recover the harmful effect of ASA on the parameters related to the male reproductive system.